Islamic Social Finance for Inclusive Growth in Indonesia: A Systematic Review of the Evidence, Synthesized Frameworks, and Future Research Directions - Muhammad Putra Aprullah; Raida Fuadi; Rita Meutia; Indrayani; Muhammad Sayuthi; Agus Adria; Salsabilla Julnadi; Zahara (AMAL: Jurnal Ekonomi Syariah, 2026)
Indonesia faces multidimensional challenges to escape the middle-income trap and achieve high-income status by 2045. Despite relatively stable economic growth (averaging 4.9% from 2000 to 2022), poverty reduction has stagnated at around 10 %, indicating that conventional economic growth is insufficiently inclusive. On the other hand, Indonesia, with the world's largest Muslim population and ranked first in the 2021 World Giving Index, has tremendous potential for developing Islamic Social Finance (ISF). This article uses a Systematic Literature Review (SLR) method to critically analyze the strategic role of ISF instruments—particularly Zakat, infaq/sedakh, and waqf—in accelerating poverty alleviation, reducing inequality, and supporting inclusive economic development in Indonesia. The study revealed that the estimated national zakat potential of IDR 327 trillion could fund up to 76% of the government's social protection budget. Meanwhile, cash waqf offers a sustainable social investment model for long-term financing in the education, health, and MSME empowerment sectors. However, the optimization of ISF remains hampered by challenges in literacy, governance, transparency, and policy integration. This study concludes that ISF is not merely a philanthropic instrument, but rather a powerful complementary policy to strengthen the government's fiscal policy towards achieving a sovereign and equitable Golden Indonesia 2045.